Effect of a nutritional intervention on iron status and body composition in elite Japanese badminton players - Matsumoto, N.; Iizuka, T.; Chino, K.; Park, J. B.; Dohi, M.; Kamei, A. (Sports Science in Elite Athlete Support, 2016)
Elite Japanese badminton players who compete at the international level are continuously traveling worldwide to participate in tournaments. It is important that they have knowledge of nutrition so they can obtain adequate nourishment to maintain their physical condition regardless of their location. However, because of nutritional and dietary problems, many players have difficulty maintaining the iron status and body composition necessary to compete in high-level tournaments. We undertook a 6-month nutritional intervention in 11 elite female Japanese badminton players who compete at the international level to examine whether improvement in their knowledge of nutrition would affect their iron status and body composition. Serum ferritin concentration tended to increase after the intervention. Further, there was a significant decrease in body fat percentage and a significant increase in lean body mass. These findings demonstrate that a 6-month nutritional intervention to improve badminton players` knowledge of nutrition is effective for maintaining and improving their physical condition.